Let's Change the Playground Floor! - Duarte, L.; Ferreira, R. (Open Schools Journal for Open Science, 2020)
This project aims at the requalification of the floor of the school’s playground. Students organized class assemblies and students’ representative assemblies, and during these meetings they identified as a problem the floor full of irregular pebbles in the playground, very popular equipment in school. The pebbles have caused some accidents and, when it rains, they take a long time to dry, preventing the use of the park. During the assemblies, students tried to find ways to solve the problem: they collected information, talked to parents and contacted different entities. The project is still ongoing but has already allowed students to learn much from it.